(untitled) (PETITUM, 2022)
ABSTRACT: This study uses normative legal research by examining various related legal regulations such as Law No. 8 of 1999 concerning consumer protection (UUPK), Law of the Republic of Indonesia Number 29 of 2004 concerning Medical Practice, and Law of the Republic of Indonesia Number 36 2009 concerning Health, as well as literature containing theoretical concepts which are then linked to the problems that are the object of this research. The results of the research show that this consumptive culture and beauty trend has caused many people to compete to improve the condition of their faces and bodies so that they can comply with today’s beauty standards. It’s just that the patient’s lack of knowledge to understand their needs for health and beauty as well as knowledge regarding their rights and obligations in receiving services, the patient’s own desire to get fast treatment results, causes most of the disadvantaged people to be reluctant to take legal action to get justice, both compensation and compensation. physical and psychological rehabilitation. ABSTRAK: Penelitian ini menggunakan penelitian hukum normatif dengan cara mengkaji berbagai aturan hukum terkait seperti Undang-Undang No.8 Tahun 1999 tentang perlindungan konsumen (UUPK), Undang-undang Republik Indonesia Nomor 29 Tahun 2004 tentang Praktik Kedokteran, dan Undang-undang Republik Indonesia Nomor 36 Tahun 2009 tentang Kesehatan, serta literatur yang berisi konsep teoritis yang kemudian dihubungkan dengan permasalahan yang menjadi objek dalam penelitian ini. Hasil penelitian menunjukkan budaya konsumtif dan tren kecantikan ini menyebabkan masyarakat banyak yang berlomba-lomba untuk memperbaiki kondisi wajah dan tubuhnya agar bisa sesuai dengan standar kecantikan masa kini. Hanya saja minimnya pengetahuan pasien untuk memahami kebutuhannya untuk kesehatan dan kecantikan serta pengetahuan terkait hak dan kewajibannya dalam menerima pelayanan, keinginan pasien sendiri untuk mendapatkan hasil perawatan yang cepat, menyebabkan sebagian besar masyarakat yang dirugikan enggan untuk melakukan upaya hukum demi mendapatkan keadilan baik ganti rugi maupun rehabilitasi fisik dan psikis.